6b-3=5a+1

Simple and best practice solution for 6b-3=5a+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6b-3=5a+1 equation:


Simplifying
6b + -3 = 5a + 1

Reorder the terms:
-3 + 6b = 5a + 1

Reorder the terms:
-3 + 6b = 1 + 5a

Solving
-3 + 6b = 1 + 5a

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 6b = 1 + 3 + 5a

Combine like terms: -3 + 3 = 0
0 + 6b = 1 + 3 + 5a
6b = 1 + 3 + 5a

Combine like terms: 1 + 3 = 4
6b = 4 + 5a

Divide each side by '6'.
b = 0.6666666667 + 0.8333333333a

Simplifying
b = 0.6666666667 + 0.8333333333a

See similar equations:

| -4p+(-1)(1-p)=1p+(-2)(1-p) | | 118/13=u/6 | | 3/5=y/7 | | 45x+32m=6 | | 2a+6=3a-10 | | 4w-21+7w=45 | | (7y+6)-(4+6y)=8 | | -6y+12+2y=40 | | Xsquared+10x+6=0 | | -5x=1+x-4-3x | | (3c-4t)(3c+3t)= | | 7/y=11/17 | | V=u-10t | | 6x-2+5x+13=180 | | y=-8y | | 17/5=x/13 | | 5(y-2)=4y-1 | | y=-3x+13 | | -3x+12=7 | | 4x^2-84=-5x | | 7(5x+3)=(2x+19) | | a+2ax= | | 4y^2-4y+6x-15=0 | | 3.7x-46=1.2x+9 | | -3.5x+2.2=-25.8 | | 2x^2-5x+a=0 | | 7(5x+4)=(2x+19) | | 7(3x/1)=-1 | | 4n^2+16n+12=0 | | 5x-7=0.5(10+2x) | | 5+-5=5+-7 | | X^3+12x^2+36=0 |

Equations solver categories